From the day they are born: a qualitative study exploring violence against children with disabilities in West Africa - Janet Njelesani; Goli Hashemi; Cathy Cameron; Deb Cameron; Danielle Richard; Penny Parnes (BMC, 2018)
Abstract Background Despite the building evidence on violence against children globally, almost nothing is known about the violence children with disabilities in low and middle-income countries (LMICs) experience. The prevalence of violence against children with disabilities can be expected to be higher in LMICs where there are greater stigmas associated with having a child with a disability, less resources for families who have children with disabilities, and wider acceptance of the use of corporal punishment to discipline children. This study explores violence experienced by children with disabilities based on data collected from four countries in West Africa- Guinea, Niger, Sierra Leone, and Togo. Methods A qualitative study design guided data generation with a total of 419 children, community members, and disability stakeholders. Participants were selected using purposive sampling. Stakeholders shared their observations of or experiences of violence against children with disabilities in their community in interviews and focus groups. Thematic analysis guided data analysis and identified patterns of meaning among participants' experiences. Results Results illuminate that children with disabilities experience violence more than non-disabled children, episodes of violence start at birth, and that how children with disabilities participate in their communities contributes to their different experiences of violence. Conclusions The study recommends policy-oriented actions and prevention programs that include children and their families in strategizing ways to address violence.